The Influence of Work Environment and Career Development on Turnover Intention With Coaching as an Intervening Variable - Dwi Agustina; Intan Silviana Mustikawati; Erry Yudhya Mulyani (Lentera Perawat, 2025)
Work environment and career development are crucial factors influencing turnover intention among nurses. Coaching can act as an intervening variable that strengthens the relationship between these factors and turnover intention. This study aims to explore the influence of work environment and career development on turnover intention, with coaching as an intervening variable at Eka Hospital Bekasi. Methods: This research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to 110 nurses at Eka Hospital Bekasi. Data analysis was conducted using univariate, bivariate, and multivariate analyses to understand the relationships between variables. Results: The results showed that work environment and career development have a significant influence on turnover intention. Coaching has a positive impact on reducing turnover intention, although its effect is smaller compared to the direct influence of work environment and career development on turnover intention. Conclusion: Work environment and career development are important factors influencing turnover intention, with coaching serving as an intervening variable that can reduce nurses' intention to leave. However, more effective coaching implementation is needed to optimize its impact on turnover intention. Recommendation: Eka Hospital Bekasi should enhance the quality of its work environment and career development, and ensure the effective implementation of coaching to reduce turnover intention among nurses